Optimalisasi Penerapan Model Pembelajaran Role Playing dalam Upaya Meningkatkan Hasil Belajar Peserta Didik pada Mata Pelajaran Biologi Materi Sistem Pertahanan Tubuh Manusia: (Optimizing the Use of Role Playing Learning Models in Efforts to Improve Student Learning Outcomes in Biology Subject Material of the Immunity System) - Fadhillah, Muhammad Aslam; Amprasto, Amprasto; Nursinta, Ita (BIODIK, 2023)
One of the reasons for the low student learning outcomes is the conventional learning models or methods used by teachers. Role Playing as a learning model aims to help students solve problems by playing roles in groups. The research used was Classroom Action Research (PTK)/action research carried out by researchers directly to describe data, facts and conditions in class. This research applies a 2 cycle research pattern using the Kemmis and Mc Taggart model. This research aims to improve the learning outcomes of XI-7 students at SMAN 12 Bandung using the Role Playing learning model. Quantitative and qualitative data analysis was carried out by recapitulating and calculating the number of formative test scores in the form of pretest and posttest in each cycle. The results in cycle 1 number of students who had not completed the pretest were 11 people or 30% and the posttest was 4 students or 11% with an overall average score of 80%. In cycle 2 the number of students who had not completed the pretest was 2 people or 6% and the posttest was 0 students or 0% with an overall average cycle II obtained a percentage of 97%. The average activity and learning outcomes of students in the form of pretest and posttest in Cycle I increased by 80% in the Good category, and in Cycle II, namely 97% in the Very Good category. The application of the Role Playing learning model to class XI-7 students at SMAN 12 Bandung on the Human Body Defense System learning material can improve student learning outcomes and knowledge. Key words: Learning Outcomes, Role Playing, Action Research Abstrak. Rendahnya hasil belajar siswa salah satunya karena model atau metode pembelajaran yang dilakukan guru yang bersifat konvensional. Role Playing sebagai suatu model pembelajaran bertujuan untuk membantu siswa memecahkan persoalan dengan memainkan peran berkelompok. Penelitian yang digunakan adalah Penelitian Tindakan Kelas (PTK)/action research dilakukan oleh peneliti secara langsung untuk mendeskripsikan data, fakta dan kondisi yang ada di kelas. Penelitian ini menerapkan pola penelitian 2 siklus dengan menggunakan model Kemmis dan Mc Taggart. Penelitian ini bertujuan untuk meningkatkan hasil belajar siswa XI-7 SMAN 12 Bandung memaui model pembelajaran Role Playing. Analisis data secara kuantitaif dan kualitatif, dilakukan dengan merekapitulasi dan menghitung jumlah skor tes formatif berupa pretest dan posttest pada tiap siklus. Hasil pada Siklus I jumlah siswa yang belum tuntas di pretest 11 orang atau sebesar 30% dan posttest sejumlah 4 siswa atau sebesar 11% dengan nilai average keseluruhan mencapai 80%. Pada Siklus II jumlah siswa yang belum tuntas di pretest 2 orang atau sebesar 6% dan posttest sejumlah 0 siswa atau sebesar 0% dengan average keseluruhan siklius II diperoleh presentase senilai 97%. Rata-rata aktivitas dan hasil belajar peserta didik berupa pretest dan postest pada Siklus I meningkat yaitu 80% dengan kategori Baik, serta pada Siklus II yaitu 97% dengan kategori Baik Sekali.Â  Penerapan model pembelajaran Role Playing pada peserta didik kelas XI-7 SMAN 12 Bandung pada materi pembelajaran Sistem Pertahanan Tubuh Manusia dapat meningkatkan hasil belajar maupun pengetahuan peserta didik. Kata kunci: Hasil Belajar, Role Playing, Penelitian Tindakan Kelas